Induction of Potent Immune Responses by Cationic Microparticles with Adsorbed Human Immunodeficiency Virus DNA Vaccines - O'Hagan, Derek (American Society for Microbiology, 2001)
The effectiveness of cationic microparticles with adsorbed DNA at inducing immune responses was investigated in mice, guinea pigs, and rhesus macaques. Plasmid DNA vaccines encoding human immunodeficiency virus (HIV) Gag and Env adsorbed onto the surface of cationic poly(lactide-coglycolide) (PLG) microparticles were shown to be substantially more potent than corresponding naked DNA vaccines. In mice immunized with HIV gag DNA, adsorption onto PLG increased CD8(+) T-cell and antibody responses by ∼100- and ∼1,000-fold, respectively. In guinea pigs immunized with HIV env DNA adsorbed onto PLG, antibody responses showed a more rapid onset and achieved markedly higher enzyme-linked immunosorbent assay and neutralizing titers than in animals immunized with naked DNA. Further enhancement of antibody responses was observed in animals vaccinated with PLG/DNA microparticles formulated with aluminum phosphate. The magnitude of anti-Env antibody responses induced by PLG/DNA particles was equivalent to that induced by recombinant gp120 protein formulated with a strong adjuvant, MF-59. In guinea pigs immunized with a combination vaccine containing HIV env and HIV gag DNA plasmids on PLG microparticles, substantially superior antibody responses were induced against both components, as measured by onset, duration, and titer. Furthermore, PLG formulation overcame an apparent hyporesponsiveness of the env DNA component in the combination vaccine. Finally, preliminary data in rhesus macaques demonstrated a substantial enhancement of immune responses afforded by PLG/DNA. Therefore, formulation of DNA vaccines by adsorption onto PLG microparticles is a powerful means of increasing vaccine potency.